The Improvement of Arabic Language Learning Program in Realizing the World Class University - Mustofa, Syaiful; Febriani, Suci Ramadhanti; Ibrahim, Faisal Mahmoud (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2021)
Foreign language is one of the fundamental elements in creating the world class university. To realize a world class university, the excellent Arabic language learning program is necessary to meet the needs of international communication in the internal and external environment of the campus. This study aimed to explore and analyze the Arabic language learning program at UIN Maliki Malang. The research data were obtained from the interview with campus governance and direct observation of Arabic learning program activities and the documentation of strategic planning of Arabic language learning programs to create a world class university. The interviews were conducted with 10 people of campus institution governance. The results showed that Arabic language learning program in realizing a world class university is an implementation of the university's vision which is contained in the development of an integrated curriculum and ulul albab character. The curriculum is designed in the form of a "tree of knowledge" construction. To form solid scientific roots, linguistic strengthening is needed so that its branches and its twigs are strong too. Language strengthening is manifested in the form of the Special Arabic Language Class Program (PKPBA), Ma'had al-jami'ah program and intensive training for educators and educational staff. These findings indicate that the integration of Arabic language learning programs between internal campus institutions is a measure of success in realizing a world class university. The recommendation for further research was to measure the effectiveness of each program at UIN Maliki Malang.